La coppia terapeutica nella comunità terapeutica - Fagioli, Massimo; Vendrame, Lucilla (Il sogno della farfalla, 2025)
This presentation was originally delivered at the Third International Group Psychotherapy Congress, held in Milan from July 18 to 21, 1963, and published the following year. Here, the authors briefly describe the methods of their clinical approach with predominantly psychotic patients at the Bellevue Clinic therapeutic community in Kreuzlingen. They specifically discuss the experimentation of a therapeutic pair (a male psychiatrist and a female social worker) conceived with the aim to evoke a concrete parental experience in patients, along with the interpersonal dynamics involved, offering the possibility of strengthening their Ego.